PENGABDIAN PERANAN LITERASI FISIK SEBAGAI PENGABDIAN MASYARAKAT BERBUDAYA OLAHRAGA DI DESA CISAAT, JAWA BARAT - Aryati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract This community service activity aims to provide socialization of the role of physical literacy on sports culture for kindergarten teachers in the Cisaat Village area, Ciater District, Subang Regency, West Java. Early Childhood requires active movement 3 hours a day (WHO2019). Cultivating sports by providing knowledge and practicing physical literacy will show many positive influences in early childhood where teachers as friends, models, motivators, facilitators are the spearhead of the implementation of learning by playing. Teachers who still need a lot of support such as teacher clothes that help movement more freely. Learning through movement is highly recommended and plus hours of activity. A good change in the level of development of early childhood as the